2018
DOI: 10.1016/j.jbo.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

NPNT promotes early-stage bone metastases in breast cancer by regulation of the osteogenic niche

Abstract: Patients with breast cancer are often afflicted by bone metastases, while the establishment and growth of bone metastases depend on interaction between cancer cells and the host environment. Moreover, osteoblasts, which play a vital role in cancer cells survival and colonization, can form an osteogenic niche in early stage of bone metastases. Also, it is widely accepted that there is a genetic determinant during bone metastases. Nephronectin (NPNT) is an extracellular matrix protein which has shown biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This clinically undetectable stage of metastasis was less characterized until recently. Several molecules and pathways have been identified by us and other groups to play important roles at this stage of bone metastasis, including VCAM-1-integrins, adhesion and gap junction proteins, IRF7, MSK1, and nephronectin [61][62][63][64][65][66]. For instance, we found that bone micrometastases predominantly reside in an osteogenic niche [62].…”
Section: The Course Of Bone Colonizationmentioning
confidence: 65%
“…This clinically undetectable stage of metastasis was less characterized until recently. Several molecules and pathways have been identified by us and other groups to play important roles at this stage of bone metastasis, including VCAM-1-integrins, adhesion and gap junction proteins, IRF7, MSK1, and nephronectin [61][62][63][64][65][66]. For instance, we found that bone micrometastases predominantly reside in an osteogenic niche [62].…”
Section: The Course Of Bone Colonizationmentioning
confidence: 65%
“…Genes such as NKD1 [Wang et al 2017] and TNFRSF19 [Guo et al 2020] were liable for proliferation of hepatocellular carcinoma cells, but these genes may be linked with development of proliferation of hepatoblastoma cells. NPNT (nephronectin) was associated with invasion of breast cancer cells [Wang et al 2018], but this gene may be responsible for invasion of hepatoblastoma cells. Decrease expression of tumour suppressor genes such as C3P1 [Zhong et al 2018], SLC22A1 [Grimm et al 2016], RDH16 [Zhu et al 2020], HAO2 [Mattu et al 2016] and GLS2 [Kuo et al 2016] were linked with progression of hepatocellular carcinoma, but low expression of these genes may associated with invasion of hepatoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…SNP in enriched genes such as ADH1B [Shih et al 2018], NAT2 [Farker et al 2003], CYP1A1 [Abo-Hashem et al 2016], CYP2D6 [Agundez et al 1996], GSTA1 [Akhdar et al 2016], MBL2 [Wang et al 2016] C6 [Wang et al 2016] and SERPINE1 [Divella et al 2015] were linked with advancement of hepatocellular carcinoma, but these polymorphic genes may be responsible for progression of hepatoblastoma. Enriched genes such as KMO (kynurenine 3-monooxygenase) [Jin et al 2015], HMGCS2 [Wang et al 2019], LIPG (lipase G, endothelial type) [Cadenas et al 2019], PON3 [Cai et al 2016], AASS (aminoadipate-semialdehyde synthase) [Xue et al 2019], PCK2 [Liu et al 2012], PPARGC1A [Wang et al 2018] and JUNB (JunB proto-oncogene, AP-1 transcription factor subunit) [Kim et al 2001] were associated with proliferation of hepatocellular carcinoma cells, but these genes may be associated with proliferation of hepatoblastoma cells. Enriched genes such as CYP1A2 [Biazi et al 2017], ADH4 [Wei et al 2012], ACSL1 [Cui et al 2014], UGT2B4 [Wijayakumara et al 2017], ALDH1A1 [Yan et al 2016], PON1 [Shu et al 2017], ASS1 [Frulio et al 2019], AKR1D1 [Nikolaou et al 2019], PTGS2 [Chen et al 2019], NNMT (nicotinamide N-methyltransferase) [Kim et al 2009], GPT (glutamic--pyruvic transaminase) [Shimokawa et al 1977], NNT (nicotinamide nucleotide transhydrogenase) [Lu et al 2017] and PCK1 [Xiang et al 2020] were linked with metabolic activity in hepatocellular carcinoma, but these genes may be involved in metabolic activity in hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that disruption of Npnt expression in the anterior ocular tissues via RCAS-mediated knockdown resulted in decreased corneal thickness. In addition to functioning in epithelial-mesenchymal interactions, Npnt has been shown to promote migration in various tissues including vascular endothelial cells during osteogenesis (Kuek et al, 2016), infiltration of immune cells into the liver (Hong et al, 2020;Inagaki et al, 2013), and cancer metastasis (Magnussen et al, 2020;Mei et al, 2020;Wang et al, 2018). Given that Npnt is localized in the primary stroma during corneal development, we hypothesized that it may play a potential role in pNC migration.…”
Section: Npnt Promotes Pnc Migration Via Rgd Domain and Itga8mentioning
confidence: 99%